Worldwide Increasing Divorce Rates: A Sociological Analysis - Mohammad Taghi Sheykhi (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2020)
The article explores how change in lifestyles has impacted the family relations leading to divorce worldwide more in industrial countries, and to a smaller extent in developing countries. Sociologically speaking, the main cause of such increase in divorce event is social change emerging due to modernization and industrialization, more education for them, change in women's consumption behavior etc. All such trends are affecting the family adjustability and the mutual respect and tolerance, leading to challenges and conflicts toward divorces. Divorce, though not being a huge problem in the Western world, it is problem-creating in the developing countries. Being a stigma in many such countries, the divorced women face lots of social and economic issues. Many of such women cannot easily remarry, and eventually deviate from the right and regular way of life. The children of divorce also lose a lot of advantages such as socialization, family/parents' affections etc. The method of research used in the present article is of qualitative type. In conclusion, it is proved that in societies with minimum divorce, more family and social health could be maintained.